piRNA-guided intron removal from pre-mRNAs regulates density-dependent reproductive strategy. - He, J.; Zhu, Y.N.; Wang, B.; Yang, P.; Guo, W.; Liang, B.; Jiang, F.; Wang, H.; Wei, Y.; Kang, L. (Cell reports, 2022)
Animal density-dependent experiences have profound effects on reproductive strategies with marked fecundity differences. Migratory locust adopts distinct population density-dependent reproductive strategies to cope with their respective life cycles, but the mechanisms remain poorly understood. Here, we report that Piwi-interacting RNAs (piRNAs) in the locust germline play key roles in this process. We find that the locust Piwi protein Liwi1 and piRNAs are highly expressed in early developing egg chambers in solitarious locusts, which have higher fecundity than gregarious locusts. Approximately 40% of solitarious locust-associated piRNAs map to protein-coding genes. We find that Liwi1/piRNAs facilitate pre-mRNA splicing of oocyte development-related genes, such as oo18 RNA-binding protein (Orb), in the germline by recruiting the splicing factor U2AF35 to piRNA-targeted introns, thereby increasing fecundity. Such piRNA-guided pre-mRNA splicing is also functional in Drosophila and mouse germ cells. We uncover a piRNA-guided splicing mechanism for processing reproduction-related mRNAs and determining animal reproductive strategies.